Enhanced primary ciliogenesis via mitochondrial oxidative stress activates AKT to prevent neurotoxicity in HSPA9/mortalin-depleted SH-SY5Y cells - Ji-Eun Bae; Soyoung Jang; Joon Bum Kim; Hyejin Hyung; Na Yeon Park; Yong Hwan Kim; So Hyun Kim; Seong Hyun Kim; Jin Min Ha; Gyeong Seok Oh; Kyuhee Park; Kwiwan Jeong; et al. (Molecular Brain, 2023)
Abstract The primary cilium, an antenna-like structure on the cell surface, acts as a mechanical and chemical sensory organelle. Primary cilia play critical roles in sensing the extracellular environment to coordinate various developmental and homeostatic signaling pathways. Here, we showed that the depletion of heat shock protein family A member 9 (HSPA9)/mortalin stimulates primary ciliogenesis in SH-SY5Y cells. The downregulation of HSPA9 enhances mitochondrial stress by increasing mitochondrial fragmentation and mitochondrial reactive oxygen species (mtROS) generation. Notably, the inhibition of either mtROS production or mitochondrial fission significantly suppressed the increase in primary ciliogenesis in HSPA9-depleted cells. In addition, enhanced primary ciliogenesis contributed to cell survival by activating AKT in SH-SY5Y cells. The abrogation of ciliogenesis through the depletion of IFT88 potentiated neurotoxicity in HSPA9-knockdown cells. Furthermore, both caspase-3 activation and cell death were increased by MK-2206, an AKT inhibitor, in HSPA9-depleted cells. Taken together, our results suggest that enhanced primary ciliogenesis plays an important role in preventing neurotoxicity caused by the loss of HSPA9 in SH-SY5Y cells.